2019
DOI: 10.1186/s13020-019-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic observation and analysis of metabolic response to moxibustion stimulation on ethanol-induced gastric mucosal lesions (GML) rats

Abstract: Background Gastric mucosal lesion (GML) is the initiating pathological process in many refractory gastric diseases. And moxibustion is an increasingly popular alternative therapy that prevents and treats diseases. However, there are few published reports about developing pathology of GML and therapeutic mechanism of moxibustion treatment on GML. In this study, we investigated pathology of GML and therapeutic mechanism of moxibustion treatment on GML. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Metabolomics strategies are fully complied with the holistic and multi-target characteristics of TCM 12 and have been successfully applied to explore the biochemical mechanisms of moxibustion therapy in the treatment of irritable bowel syndrome (IBS) 13 , gastric mucosal lesions (GML) 14 , and chronic atrophic gastritis (CAG). 15 Nevertheless, there have been no studies specifically focusing on the metabolic alterations corresponding to moxibustion interventions for AS.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics strategies are fully complied with the holistic and multi-target characteristics of TCM 12 and have been successfully applied to explore the biochemical mechanisms of moxibustion therapy in the treatment of irritable bowel syndrome (IBS) 13 , gastric mucosal lesions (GML) 14 , and chronic atrophic gastritis (CAG). 15 Nevertheless, there have been no studies specifically focusing on the metabolic alterations corresponding to moxibustion interventions for AS.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of this study. Our previous studies also showed that electro-acupuncture can repair gastric mucosal glands and reduce inflammatory infiltration [ 7 , 12 , 14 16 , 20 – 22 ]. The above studies confirmed that electro-acupuncture can protect gastric mucosa and reduce the symptoms of GML.…”
Section: Discussionmentioning
confidence: 99%
“…Increased studies have confirmed the interaction between stomach and CNS [ 13 ]. As a macro observation method, NMR-based metabonomics has advantages for observing the reinforcement between stomach and CNS, it can simultaneously and comprehensively observe the changes of metabolites in stomach and brain, and observe the brain stomach interaction of GML from a more wide perspective [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that high concentrations of LysoPCs could active neutrophils and macrophage and cause oxidative stress damage in the cell membrane [79]. Previously, moxibustion had exerted a protective effect on cell membrane of rats with ethanol-induced gastric mucosal lesions through down-regulating the serum levels of LysoPCs [31]. Similarity, the levels of three LysoPCs compounds are reversed by moxibustion at GV4, BL23 and ST36, suggesting that moxibustion at speci c acupuncture points treatment has the ability to ameliorate the cellular injury in AS.…”
Section: Lipid Metabolism Pathwaymentioning
confidence: 99%